Perencanaan Pintu Pelimpah Bendungan Margatiga Kabupaten Lampung Timur Provinsi Lampung - Susanti, Lidya; Purwanto, Eddy; Wahono, Endro Prasetyo (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
AbstractSpillway has an important role for both operating rules as well as a safety structure, particularly during flood, of a dam. In Margatiga Dam, gated-spillways were designed in order to regulate discharge to downstream mainly for irrigation purpose. The Margatiga Dam, located in East Lampung Regency, is a rock fill type of dam with vertical core, formed from specific clay materials. The dam was designed to supply the Sragi’s irrigation area mostly located in East Lampung Regency, which has more than 80% of its citizen are farmers. The main objective of this research is to design gate leaf structure of the spillway, in the form of skin plates and beams that fulfill safety requirement of the structure. Design was performed for two conditions, which are during normal water level, and during the flood conditions. Based on those two conditions, the most extreme forces was selected as the basis of the structural design. The loads, which are used for design, consist of hydrostatic pressure, sediment pressure, dynamic pressure during the earthquake, and the hydrodynamic pressure. This research provide dimension of the gate leaf of the concerned spillway. Thickness of the steel plates is 13 mm, meanwhile the dimension of girder plates are 900x300 mm, 860x100 mm, and 900x150 mm, for the horizontal beams, vertical beams, and the edge of the beams respectively. Thickness of flense and web for all the beams are designed to be 13 mm and 5 mm respectively. Design of the gate provide maximum deflection of the beams for 10.06 mm and maximum deflection of the plates is 5.16 mm, which are considered to fulfill the safety requirement for the conditions during probable maximum discharge (QPMF).Keywords : spillway, gate leaf, QPMF, girder plate